2022
DOI: 10.1002/ccr3.6310
|View full text |Cite
|
Sign up to set email alerts
|

Hyperreactio luteinalis associated with fetal hyperandrogenism and cystic hygroma

Abstract: A 23‐year‐old woman with a gestational age of 17 weeks presented with abdominal pain. The ultrasound showed maternal hyperreactio luteinalis with fetal cystic hygroma. After termination of pregnancy, the female fetus showed masculinization features with muscular hypertrophy. The hyperreactio luteinalis regressed under hormonal suppression therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
0
0
Order By: Relevance
“…Elevated thyroid-stimulating hormone levels may contribute to the development of HL through cross-reactivity with human chorionic gonadotropin and follicle-stimulating hormone receptors. Ghassan et al suggested that luteal hyperresponsiveness is associated with fetal hyperandrogenemia and cystic hydrops [ 5 ]. In the present case, the fetus was normal, and the mother did not show signs of hyperandrogenemia.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated thyroid-stimulating hormone levels may contribute to the development of HL through cross-reactivity with human chorionic gonadotropin and follicle-stimulating hormone receptors. Ghassan et al suggested that luteal hyperresponsiveness is associated with fetal hyperandrogenemia and cystic hydrops [ 5 ]. In the present case, the fetus was normal, and the mother did not show signs of hyperandrogenemia.…”
Section: Introductionmentioning
confidence: 99%